Energy Poverty, Institutional Reform and Challenges of Sustainable Development: The Case of India. (April 2017) - Jewitt, Sarah; Raman, Sujatha
This article 1 assesses recent efforts by the Indian government to tackle energy poverty and sustainable development. It focuses on the new integrated energy policy and initiatives to disseminate improved cookstoves and develop energy alternatives for transport. The success of government initiatives in cleaner biomass cookstoves and village electrification has historically been limited, and institutional reforms in the 2000s promoted market-led and 'user-centred' approaches, and encouraged biofuels as a 'pro-poor' route to rural development and energy security. The article argues that such interventions have reopened tensions and conflicts around land-use, intra-community inequalities and the role of corporate agendas in sustainable energy.